Mirror proteases of Ac-Trypsin and Ac-LysargiNase precisely improve novel event identifications in Mycolicibacterium smegmatis MC2 155 by proteogenomic analysis - Jiang, Songhao; Shi, Jiahui; Li, Yanchang; Zhang, Zhenpeng; Chang, Lei; Wang, Guibin; Wu, Wenhui; Yu, Liyan; Dai, Erhei; Zhang, Lixia; Lyu, Zhitang; Xu, Ping; et al. (Frontiers in Microbiology, 2022)
Accurate identification of novel peptides remains challenging because of the lack of evaluation criteria in large-scale proteogenomic study. Mirror proteases of trypsin and lysargiNase can generate complementary b/y ion series, providing the opportunity to efficiently assess authentic novel peptides in experiment other than to filter potential targets by different false discovery rates (FDRs) ranking. In this study, a pair of in-house developed acetylated mirror proteases, Ac-Trypsin and Ac-LysargiNase, were used in Mycolicibacterium smegmatis MC2 155 for proteogenomic analysis. Mirror proteases accurately identified 368 novel peptides, exhibiting 75-80% b and y ion coverages against 65-68% y or b ion coverages of Ac-Trypsin (38.9% b and 68.3% y) or Ac-LysargiNase (65.5% b and 39.6% y) as annotated peptides from M. smegmatis MC2 155. Complementary b and y ion series largely increased reliability of overlapped sequences derived from novel peptides. Among these novel peptides, 311 peptides were annotated in another public M. smegmatis strains, and 57 novel peptides with more continuous b and y pairs were obtained for further analysis after spectral quality assessment. This enabled mirror proteases to successfully correct 6 annotated protein’s N-termini and detect 17 new coding open reading frames (ORFs). We believe that mirror proteases will be an effective strategy for novel peptide detection on both prokaryotic and eukaryotic proteogenomics.